2022
DOI: 10.5761/atcs.oa.21-00167
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Low Serum Calcium Levels Predict Poor Prognosis for Patients with Esophageal Cancer

Abstract: Purpose: Hypercalcemia has been reported as a poor prognostic factor in malignant tumors. However, no report has shown the clinical impact of serum calcium levels on patients with esophageal cancer. We evaluated the prognostic impact of preoperative serum calcium levels on patients with esophageal cancer. Methods: We evaluated 240 patients (197 men, 43 women; mean age, 66 years; age range, 34-85 years) with esophageal cancer who underwent radical surgery between September 2008 and December 2017. After assignin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In our study, patients in the active phase had significantly higher levels of inflammatory indicators than those in either the remission or the control group (Tables 1 and 2). Previous studies have shown that magnesium and calcium are effective antagonists of cytokines 9,10,22,26,27 . One possible explanation for these findings is that there may be an interaction between an individual's inflammatory status and his or her magnesium and calcium levels.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In our study, patients in the active phase had significantly higher levels of inflammatory indicators than those in either the remission or the control group (Tables 1 and 2). Previous studies have shown that magnesium and calcium are effective antagonists of cytokines 9,10,22,26,27 . One possible explanation for these findings is that there may be an interaction between an individual's inflammatory status and his or her magnesium and calcium levels.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it has been shown that magnesium may be a sensitive marker for the activity of small bowel disease 25 . Low calcium concentrations are also closely associated with the progression and poor prognosis of oesophageal cancer, which was also a disease of the digestive tract 26 . Taking all these factors into consideration, we propose that magnesium and calcium may be used as auxiliary markers in addition to the existing assessment methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations